Narrative and prosodic skills in children and adolescents with Down syndrome and typically developing children. (4th May 2021) - Zanchi, Paola; Zampini, Laura; Panzeri, Francesca
Abstract: Purpose: Children with Down Syndrome (DS) show difficulties in language development, in both basic and complex abilities, as narratives. Less is known about the prosodic competence in DS, but the few available studies highlighted the presence of some deficits. Considering the importance of narratives and prosody in communication, the main aim of this study is to investigate these two competencies in participants with DS. Method: 13 children with DS participated (Mean age: 13;04, years; months). Their narrative and prosodic abilities, collected through a storytelling task, were compared with those of two control groups of typically developing (TD) children, one matched for nonverbal mental age (MA, Mean age: 5;03) and the other matched for the mean length of utterance (MLU, Mean age: 5;05). For the narrative competence, we considered both the macrostructural (i.e. quantity of information and story structure) and the microstructural level (i.e. verbal productivity, lexical diversity, syntactic complexity). For the prosodic competence, we took into account acoustic measures linked to intonation (i.e. mean fundamental frequency (f0), pitch range, final speech profile, and speed of speech). Result: The results of the Mann-Whitney test showed that participants with DS produced stories comparable to those of TD children in nearly all the variables considered, except for the syntactic complexity when compared with children of the same MA. Differences between participants with DS and TD children were found in the f0 and the final pitch profile used. Conclusion: Considering the small size of the samples, these preliminary results should be taken with caution. Nonetheless, this study confirms the presence of difficulties in the prosody of speech and in the syntactic competence of children with DS. These difficulties could have consequences on the possibility to communicate efficiently and should be taken into account in rehabilitation programmes.